Achieving Effective Multimodal Imaging with Rare-Earth Ion-Doped CaF2 Nanoparticles - Zhenfeng Yu; Yuanyuan He; Timo Schomann; Kefan Wu; Yang Hao; Ernst Suidgeest; Hong Zhang; Christina Eich; Luis J. Cruz (MDPI AG, 2022)
Nowadays, cancer poses a significant hazard to humans. Limitations in early diagnosis techniques not only result in a waste of healthcare resources but can even lead to delays in diagnosis and treatment, consequently reducing cure rates. Therefore, it is crucial to develop an imaging probe that can provide diagnostic information precisely and rapidly. Here, we used a simple hydrothermal method to design a multimodal imaging probe based on the excellent properties of rare-earth ions. Calcium fluoride co-doped with ytterbium, gadolinium, and neodymium (CaF2:Y,Gd,Nd) nanoparticles (NPs) is highly crystalline, homogeneous in morphology, and displays a high biosafety profile. In addition, in vitro and ex vivo experiments explored the multimodal imaging capability of CaF2:Y,Gd,Nd and demonstrated the efficient performance of CaF2:Y,Gd,Nd during NIR-II fluorescence/photoacoustic/magnetic resonance imaging. Collectively, our novel diagnosis nanoparticle will generate new ideas for the development of multifunctional nanoplatforms for disease diagnosis and treatment.